2014
DOI: 10.1016/j.nds.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Precise Lifetime Measurements in Light Nuclei for Benchmarking Modern Ab-initio Nuclear Structure Models

Abstract: A new generation of ab-initio calculations, based on realistic two-and three-body forces, is having a profound impact on our view of how nuclei work. To improve the numerical methods, and the parameterization of 3-body forces, new precise data are needed. Electromagnetic transitions are very sensitive to the dynamics which drive mixing between configurations. We have made a series of precise (<3%) measurements of electromagnetic transitions in the A=10 nuclei 10 C and 10 Be by using the Doppler Shift Attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…By impinging the beam onto a 2 H gas cell at 800 Torr, we produced 7 Be through the 6 Li( 2 H, n) 7 Be reaction. The secondary 7 Be beam had an energy of 31.3 (10) MeV and was collected and separated from competing reaction products using the two superconducting solenoid magnets of TwinSol [45]. A diagram of the TwinSol beamline is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By impinging the beam onto a 2 H gas cell at 800 Torr, we produced 7 Be through the 6 Li( 2 H, n) 7 Be reaction. The secondary 7 Be beam had an energy of 31.3 (10) MeV and was collected and separated from competing reaction products using the two superconducting solenoid magnets of TwinSol [45]. A diagram of the TwinSol beamline is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, electromagnetic observables can provide a stringent test of ab initio nuclear theory. For instance, several electromagnetic transition strengths have been determined to high precision in A = 10 nuclei using lifetime and branching ratio measurements and then compared to ab initio quantum Monte Carlo calculations [8][9][10][11]. It was found that the calculated E2 transition strengths were sensitive to the threebody interaction used.…”
Section: Introductionmentioning
confidence: 99%